Effect of age on the viability of pig intestinal explants: a histological and ultrastructural approach - Basso, Karina M.; Bracarense, Ana Paula F.R.L. (Archives of Veterinary Science, 2015)
Intestinal explants are a useful model for toxicological and pathological studies, but the maintenance of tissue viability for longer periods of incubation remains challenging. The aim of this study was to evaluate the effect of age on the viability of intestinal explants. Jejunal explants were obtained from 24- and 42-day-old piglets. The explants were incubated for two or four hours and were then processed for histological analysis. The explants from younger pigs showed minor histological changes, as assessed by histological and morphometrical scores. Explants from 24-day-old pigs were incubated for four hours and subjected to ultrastructural analysis to assess cell integrity. The plasma membranes, nuclei and organelles of enterocytes were well preserved, and adsorptive endocytosis was observed. In conclusion, the data indicate that the age of the donor influences explant viability. The intestinal morphology of incubated explants from young donors was better preserved than that of explants from older piglets.